Sex differences in health-related quality of life among adults in the US: results from the medical expenditures panel survey data - Monira Alwhaibi; Bander Balkhi (BMC Public Health)
Abstract Background Sex disparities in health represent a significant challenge for many nations’ healthcare systems. Sex disparities in health-related quality of life (HRQoL) remain insufficiently explored at the population level, despite evidence suggesting that women consistently report lower HRQoL than men. Most prior studies have been disease-specific, relied on small samples, or treated sex as a control variable rather than a primary focus. This study aims to address this gap by evaluating sex differences in HRQoL among U.S. adults using nationally representative data, while accounting for a broad range of social, behavioral, and health-related determinants. Methods A cross-sectional analysis was conducted using data from the Medical Expenditure Panel Survey (MEPS) for 2020–2021, including 8,482 men and 10,235 women aged 18 and 64. HRQoL was measured using the veterans RAND 12 item health survey which has two domains the Physical and Mental Component Summary (PCS & MCS). The relationships between HRQoL and sex were investigated using a linear regression model after the adjustment for covariates. Results Women reported lower mean HRQoL than men in the physical domain (51.08 vs. 52.05) and the mental domain (50.05 vs. 51.79). After adjusting for covariates in the linear regression analysis, women had a lower HRQOL compared to men in both the physical domain (PCS: β = -0.090, p-value < 0.0001) and the mental domain (MCS: β = -0.643, p-value < 0.0001). Employment, high income, good perceived general health, and being physically active were positively related to HRQoL, while having high education, health insurance, and chronic illnesses were negatively associated with HRQoL. Notably, employment was positively related to the physical domain of HRQoL in men but positively associated with the physical and mental domains of HRQoL in women. Depression was negatively related to the physical and mental domains of HRQoL in women but only associated with mental domains in men. Conclusions This study’s findings reveal significant sex disparities in adult HRQoL, with women reporting lower HRQoL. The variations in socioeconomic and clinical characteristics and aspects of HRQoL between men and women are also highlighted. These findings provide valuable insights and hope for future interventions to enhance HRQoL among women at risk of low HRQoL.